Isolation of Escherichia Coli and Staphylococcus Aureus in Surface Water Sources in Katabi Subcounty, Wakiso District. - Mabonga, Habert (Student’s Journal of Health Research Africa, 2021)
Background: Unsafe water, inadequate sanitation, and insufficient hygiene account for an estimated 9.1 percent of the global burden of disease and 6.3 percent of all deaths. This study aimed to isolate Escherichia coli and staphylococcus aureus in surface water sources in Katabi Subcounty, Wakiso District. The specific objectives were to isolate E.coli and Staphylococcus aureus in water sources in the Katabi sub-county and to determine the physico-chemical parameters of the water sources. Methodology: A cross-sectional and snowball sampling method was applied while collecting water samples from the wells, boreholes, and other groundwater in the selected areas of Wakiso District (Katabi division, and Kajjasi division). Results: A total of 34 (n=34) water samples were obtained including borehole water 61.8% (n1=21/34), spring water 11.8% (n2=4/34) and open well water 26.4% (n3=9/34). Freshwater samples were directly analyzed from the water source for pH, temperature, and dissolved oxygen, then different means of physic-chemical parameters were recorded, Mean temperature for open well water was 23.5°C±1.092, pH=5.21±0.432, and dissolved oxygen was 4.075±1. 555). The mean temperature for spring water was 22.98°C±0.907, pH=5.7± 0.781, and dissolved oxygen was 4.075±1.555. For borehole water, the mean temperature was 22.9°C±1.339, pH=5.7±1.441, and dissolved oxygen was 4.9±1.549). A total of 10 samples fermented MSA after overnight incubation at 37°C changing the media color from pink to yellow, borehole water samples were 60% (6), spring water samples were 20% (2) and open well water samples were 20% (2). Also, S. saprophyticus 76.9% (10) and S.epidermidis 23.1% (3) were identified. Conclusion and recommendation: All the samples analyzed did not show growth of E.coli and S.aureus but had other organisms including S.saprophyticus and S.epidermidis which could be harmful to human health when consumed. Further investigation of possible pathogenic organisms that are present in drinking water under the acidic pH should be done.